2018
DOI: 10.1002/brb3.1157
|View full text |Cite
|
Sign up to set email alerts
|

Implicit but not explicit extinction to threat‐conditioned stimulus prevents spontaneous recovery of threat‐potentiated startle responses in humans

Abstract: IntroductionIt has long been posited that threat learning operates and forms under an affective and a cognitive learning system that is supported by different brain circuits. A primary drawback in exposure‐based therapies is the high rate of relapse that occurs when higher order areas fail to inhibit responses driven by the defensive circuit. It has been shown that implicit exposure of fearful stimuli leads to a long‐lasting reduction in avoidance behavior in patients with phobia. Despite the potential benefit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…top-down driven mechanisms. This might be an interesting topic for future research, testing whether there are differences in attention-related neural activity between implicit vs explicit extinction learning and the effects on phenomena such as extinction retrieval, spontaneous recovery, fear reinstatement and renewal ( Maren and Holmes, 2016 ; Oyarzun et al. , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…top-down driven mechanisms. This might be an interesting topic for future research, testing whether there are differences in attention-related neural activity between implicit vs explicit extinction learning and the effects on phenomena such as extinction retrieval, spontaneous recovery, fear reinstatement and renewal ( Maren and Holmes, 2016 ; Oyarzun et al. , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a decrease in brain responses to subliminal phobic stimuli following CBT suggests that this approach does not impact on the regulation of automatic attentional processes (Lipka et al, 2014) and could explain the significant vulnerability to relapse that persists following successful elimination of fear via CBT (LeDoux, 1994;Vervliet et al, 2013). Actually, subliminal stimulations have a role in activating (and properly habituating) non-conscious stimulus-processing mechanisms and in fact recent evidence supports the idea that subliminal stimulus exposure may be an effective means of reducing relapse (Oyarzún et al, 2019). As a summary, there are hints that responses to subliminal stimuli survive standard interventions involving overt stimuli exposure only, and paradigms integrating also subliminal stimuli exposure might be more effective.…”
Section: Do Phobic Subliminal Stimuli Affect Cardiac Defense Reactions?mentioning
confidence: 99%
“…Unlike the catastrophic consequences of exposure that phobic persons believe will happen, these aversive arousal and subjective fear responses are sure to happen, acting like the electric shocks (the UCS) in fear conditioning experiments. These initial, but inevitable and highly aversive fear responses to exposure are naturally occurring, internal UCSs that powerfully reinforce "Stimulus → Fear" associations-a positive feedback loop that, as studies have repeatedly shown, interferes with extinction learning (Figure 4; Hauner et al, 2013;Norrholm et al, 2015;Oyarzún et al, 2019;Siegel et al, 2017Siegel et al, , 2022Siegel & Weinberger, 2012).…”
Section: Figurementioning
confidence: 99%
“…Nonconscious extinction studies based on unconscious exposure to the fear CS yielded direct evidence of extinction learning during late extinction (Bachar-Avnieli et al, 2023), fear reinstatement , spontaneous recovery (Bachar-Avnieli et al, 2023;Oyarzún et al, 2019), and during the unconscious state of SWS (Gvozdanovic et al, 2023;Hauner et al, 2013;.…”
Section: Theoretical Organization and Interpretation Of Findings: The...mentioning
confidence: 99%
See 1 more Smart Citation